Plastik Sebagai Wadah Garam Beiodium - Anang Lukmana (Jurnal Kimia dan Kemasan, 1979)
The utilization of plastic as packaging material in the form of bag has indicated that it was the most economic and practical container, and it has widely used for salt packaging in order to avoid the salt being damaged.The hygroscopics characteristic of the iodized salt could be tolerate by polypropylene and polyetylene plastics container